The Effect of Operating Conditions on the Purification of Waste Cooking Oil over a Natural Zeolite Catalyst - Suhendi, Endang; Heriyanto, Heri; Nur Avina, Mely; Andriani, Kharina (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2022)
The waste of cooking oil is a danger to human health. The Heating of waste cooking oil at high temperatures will cause an increase in free fatty acid (FFA) and peroxide number in the oil. Therefore, waste cooking oil needs to be processed before being reused. This paper studies the effect of operation conditions on the purification of waste cooking oil over a natural zeolite catalyst. The stage of the purification process is despicing, neutralization, and bleaching process. The despicing process injected the steam to remove impurities. The effect of the mass flow rate of oil at 1.051; 0.456 and 0.139 Kg/s on FFA value was studied. After that, the neutralization and bleaching process. The Bleaching process was performed using zeolite adsorbent. The results show that the purification method of waste cooking oil decreases of the color of oil, free fatty acid, and peroxide value. In this study, the best performance of the despicing process at the mass flow rate of the oil is 0.139 Kg/s, a temperature of 60°C with 500 rpm stirring for the neutralization process and bleaching process of natural zeolite. The value of free fatty acid content (FFA) is 2.22 mg. KOH/mg fat, peroxide is 6.98 mekO2/kg, color degradation is 66.93% and water content is 0.32% (w/w).